Efficiency of commercial inoculants and native Rhizobium strains in six forage legumes on a cerrado soil - Vargas, Milton Alexandre T.; Suhet, Allert Rosa (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out with the leumes Centrosema pubescens, Stylosanthes capitata, S. bracteata, Macroptilium atropurpureum, Galactia striata and Calopogonium mucunoides in a virgin cerrado soil in order to study the efficiency of commercial inoculants and of native Rhizobium strains. The statistical design was a complete factorial 3 x 6 in randomized blocks. The treatments were: a) check, b) inoculation and c) inoculation + 75 kg/ha N. The soil was not limed, but an additional treatment of 1 t/ha of lime was included with two of the legumes. The inoculation had no effect on the forage legumes studied except for the Centrosema pubescens, where inoculation increased the nodulation, dry weight and total N of the plants, compared to the check. The treatment receiving nitrogen was the best for C. pubescens, Macroptilium atropurpureum, Calopogonium mucunoider and Galactia striata indicating that symbiósis was not efficient in these species. Under the low soil fertility conditions of the experiment, the symbiosis with the native strains was sufficient to supply all the nitrogen necessary to Stylosanthes capitata and S. bracteata. The addition of lime to Centrosema pubescens and Stylosanthes capitata improved the nodulation, total N and dry weight of plants. The results indicate that the commercial inoculants tested were not satisfactory for the species studied. The nitrogenase activity level in the treatments that received no inoculation indicates the presence of a native nitrogen-fixing microflora in the soil. The selection of Rhizobium strains from within the native population is suggested as a promising method to obtain more adequate inoculants for the "cerrados" region.